Failure to achieve pelvic balance following hip replacement surgery may be a risk factor for development of degenerative scoliosis - Asad M. Lak; Francesca Siddi; Fidelia Ida; Hasan A. Zaidi; Timothy R. Smith; Yi Lu (Interdisciplinary Neurosurgery, 2021)
Introduction: In the global alignment of body, the pelvis and spine are strictly and mutually connected. Our hypothesis was that failure to achieve pelvic balance following hip replacement surgery (THA) may be a risk factor for development of degenerative scoliosis. Methods: A retrospective case control study was conducted. Patients who underwent THA followed by spine surgery primarily because of scoliosis (scoliosis group) were compared to patients who only underwent THA (no scoliosis group). Any patient in either group who had spine surgery prior to THA was excluded. Propensity score matching was utilized to match the two groups on age, gender and etiology for THA. Results: A total of 78 patients (39 in each group) were included in the study. The mean age was 63 years in scoliosis group and 64 years in no scoliosis group. The most common etiologies for THA were osteoarthritis, fracture and avascular necrosis. The mean pelvic obliquity as measured by the O’Brien method was 2.9° (0.2–6.5) in scoliosis group and 1.1° (0–4.5) in no scoliosis group. This difference in pelvic obliquity between the two groups was statistically significant (p < 0.01). The mean time interval between THA and spine surgery was 9.5 years. The mean follow-up in scoliosis group was 12 years and 6 years in no scoliosis group. Conclusion: Altered pelvic parameters following hip surgery may be a contributing factor in the development of thoracolumbar scoliosis. Our data showed that a small change in pelvic balance following THA could pose a risk for developing degenerative scoliosis.